INFORMASI AKUNTANSI SEBAGAI ALAT PERENCANAAN STRATEGIS - Juliana Putri (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
This study aims to provide information to stakeholders users accounting information of a company in decision making. This research uses research design is explanatory (explanatory research). This research is focused on strategic planning in an organization by using accounting information as its tool. The maturity of organizational information systems planning is defined as how far the information system planning process helps create opportunities for information systems to make a strategic contribution to the organization. Accounting is applied basically all aspects of strategic management, so that accounting serves as a tool in strategic management. Keywords: accounting information, strategic planning